2014
DOI: 10.1021/ic4030712
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Reversible Electronic Energy Transfer Involving an Iridium Center

Abstract: A cyclometalated iridium complex is reported where the core complex comprises naphthylpyridine as the main ligand and the ancillary 2,2′-bipyridine ligand is attached to a pyrene unit by a short alkyl bridge. To obtain the complex with satisfactory purity, it was necessary to modify the standard synthesis (direct reaction of the ancillary ligand with the chloro-bridged iridium dimer) to a method harnessing an intermediate tetramethylheptanolate-based complex, which was subjected to acid-promoted removal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…The fitting procedure results in an activation energy (E a ) of ∼1740 cm −1 , on the larger end of the typical range observed in other triplet excited state equilibrated compounds. 21,29,35,45 The τ 1 values also increase with decreasing temperature, although the uncertainty in the higher temperature values of τ 1 did not allow for quantitative fitting. A normalized plot of the corresponding decay rates k 1 , k 2 , and k 3 revealed that k 1 and k 2 have similar temperature-dependent profiles.…”
Section: ■ Experimental Methodsmentioning
confidence: 98%
“…The fitting procedure results in an activation energy (E a ) of ∼1740 cm −1 , on the larger end of the typical range observed in other triplet excited state equilibrated compounds. 21,29,35,45 The τ 1 values also increase with decreasing temperature, although the uncertainty in the higher temperature values of τ 1 did not allow for quantitative fitting. A normalized plot of the corresponding decay rates k 1 , k 2 , and k 3 revealed that k 1 and k 2 have similar temperature-dependent profiles.…”
Section: ■ Experimental Methodsmentioning
confidence: 98%
“…Similar to the design of Ir‐7 , a bichromophoric biscyclometalated iridium complex was reported by McClenaghan et al in which a pyrene unit was attached to an auxiliary bpy ligand of the complex via a short ethylene spacer . The photophysical properties of the complex was studied with steady‐state and time‐resolved spectroscopies, and a reversible intramolecular energy transfer was also proven established within this molecule.…”
Section: Bichromophoric Transition‐metal Complex Sensitizersmentioning
confidence: 71%
“…In solutiona nd host matrices (a polymericP S3 98 membrane and an anostructured metal oxide matrix (AP200/19)), remarkably higho xygen sensitivity is observed. [24] Some bis-cyclometalated Ir III complexes (15 and 16)w ith the general formula Ir(1-phenylpyrazole) 2 (X^NPyrene), where X^NPyrene represent synthetically easily accessible bidentate chelate with X = No rO ,w erea lso reported. [25] Even subtle modifications on the pyrene-containing ligand dramatically affected the observed emission lifetimesi nt he range 0.33 to 104 ms.…”
Section: à5mentioning
confidence: 99%